Systematic Review of the Literature on Interventions to Improve Self-Regulation of Learning in First-Year University Students - David Simón-Grábalos; David Fonseca; Marian Aláez; Susana Romero-Yesa; Carlos Fresneda-Portillo (Education Sciences)
Previous research has shown a significant percentage of dropouts in university studies, particularly in the first years. Furthermore, evidence links higher motivation and curricular improvement in students when they enhance their self-regulated learning (SRL). A systematic review was conducted using the PRISMA method to identify and analyze interventions to improve SRL in first-year undergraduate students. The interventions analyzed addressed student learning, classroom management by teachers, evaluation processes, and administrative management. Additionally, the need for a holistic and continuous approach was identified, covering cognitive, metacognitive, motivational, behavioral, and affective dimensions. The combination of self-perception questionnaires and academic grades was the most used strategy to measure intervention effectiveness. These findings emphasize the importance of adapting interventions to specific contexts and ensuring their continuity to maximize the impact on the development of students’ self-regulated learning. The results reveal a high heterogeneity in the approaches applied, highlighting the most effective techniques as follows: specialized workshops, the use of virtual tools, and group and individual tutoring. Intracurricular interventions, integrated within course content and led by the faculty, demonstrated greater success by embedding SRL strategies into the teaching–learning process. In contrast, extracurricular interventions, conducted by tutors or academic advisors, faced challenges related to student motivation and participation.